Perdas de água e sedimento em bacias pareadas de ordem zero sob plantio direto com e sem terraço - Londero, Ana Lúcia (2015)
Tillage is a conservation technique for soil management, whose principles are avoiding soil disturbance, straw maintenance on the surface and crop rotation. Currently, negligence in its use leads to situations of land degradation. Little is known about the hydrological and erosive dynamic in slopes and zero-order basins. The study monitored water and soil loss in mishandled tillage systems in the scope of paired basins of order zero, with and without mechanical practices for runoff control. The plots are located in FEPAGRO Semente s experimental area in the city of Julio de Castilhos, RS Central region. The basin area without mechanical practices is 2.34 ha and with mechanical conservation practices in the form of terraces of 2.43 ha. Rainfall, flow and sediment concentration were monitored during major rainfall events that occurred between the periods of July 2014 to March 2015. The data was analyzed to understand the dynamics of water infiltration and formation of runoff in two ways: comparison of total losses of water and sediment between events, and the comparison of the hydrograph and sedimentograph of a same event between basins. The results demonstrate that the basins are highly responsive to the precipitation and that sediment production is exhausted in the duration of each event. The tillage system without mechanical practice could not contain the superficial runoff whereas in the basin where mechanical practices were used such losses were greatly reduced. For rainfall of larger magnitudes, flow rates were heightened, indicating high sediment production capacity. In the bowl with mechanical practice, construction of terraces resulted in flow rates with higher concentrations of sediment, but did not cause a higher amount of total sediments due to the low volume drained. Soil losses were significant for larger events and with low ground cover.